Gamification for tourism - Xu, Feifei 1974-; Buhalis, Dimitrios (Aspects of tourism, 2021)
"This book examines the cutting-edge concept of gamification in tourism. The chapters offer valuable insights and examples of best practice and address key issues of game mechanism and game design principles. This will be useful for students and researchers in tourism marketing, smart tourism and tourism futures, as well as industry practitioners"-- Provided by publisher.